Recording conceptual art : early interviews with Barry, Huebler, Kaltenbach, LeWitt, Morris, Oppenheim, Siegelaub, Smithson, Weiner - Barry, Robert, 1936-; Alberro, Alexander; Norvell, Patsy, 1942- (University of California Press, 2001)
Recording Conceptual Art features a highly provocative series of previously unpublished interviews conducted in early 1969 with some of the most dynamic, daring, and innovative artists of the tumultuous 1960s. The nine individuals--eight artists and one art dealer--are now known as major contributors to Conceptual art.